2016
DOI: 10.1253/circj.cj-15-1258
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Defibrillation Threshold and Minimized Myocardial Damage With Left Axilla Implantable Cardioverter Defibrillator Implantation

Abstract: Clinically and theoretically, the left axilla was shown to be an improved ICD implantation site that may reduce DFT and lessen myocardial damage due to shock. Lower DFT also facilitates less myocardial damage, as a result of the lower shock required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…An in silico study reported a lower defibrillation threshold for right-sided than for left-sided S-ICD lead placement. 29 An observational study in a general S-ICD population 30 demonstrated similar rates of successful defibrillation with the first 65J shock (79% left-sided and 73% right-sided lead; P=NS), and similar rates of ineffective shocks (2.9% left-sided and 1.9% right-sided lead; P=NS). A randomized controlled trial is needed before right-sided S-ICD lead placement can be recommended as preferential in ACHD.…”
Section: Nearly Half Of the Contemporary Achd Population Is Ineligible For S-icdmentioning
confidence: 92%
“…An in silico study reported a lower defibrillation threshold for right-sided than for left-sided S-ICD lead placement. 29 An observational study in a general S-ICD population 30 demonstrated similar rates of successful defibrillation with the first 65J shock (79% left-sided and 73% right-sided lead; P=NS), and similar rates of ineffective shocks (2.9% left-sided and 1.9% right-sided lead; P=NS). A randomized controlled trial is needed before right-sided S-ICD lead placement can be recommended as preferential in ACHD.…”
Section: Nearly Half Of the Contemporary Achd Population Is Ineligible For S-icdmentioning
confidence: 92%
“…Potential side effects of this procedure are, in addition to the anesthetic risk, skin burns, heart block, prolonged sinus arrest, ventricular pro-arrhythmia, epidermal necrosis, and apnea (Pagan-Carlo et al, 1997;Kowey et al, 1998;Yava et al, 2012). However, while most studies show no relevant myocardial damage from external eCV (Georges et al, 1996;Neumayr et al, 1997;Greaves and Crake, 1998;Walcott et al, 2003;Piechota et al, 2007;Lobo et al, 2018), there is injury to the myocardium by internal eCV (Noro et al, 2016;Stieger et al, 2018).…”
Section: Electrical Cardioversionmentioning
confidence: 99%
“…ICDs are superior to antiarrhythmic drug therapy for prevention of sudden cardiac death 60,116,123 . The position of defibrillation coils is not important provided the area between anode and cathode covers 90 % of the heart tissue with a voltage gradient of more than 5 volts per meter 129 . An ICD delivers pacing therapy when needed, since bradycardia frequently develops immediately after a shock.…”
Section: Icdmentioning
confidence: 99%